Evaluation of resistance of maize samples from the collection of the Ustymivka experimental plant production station to major pests and diseases - Kharchenko, L.; Kharchenko, M.; Pospielova, G.; Pospielov, S.; Lisovyi, V.; Lavrynenko, I. (Scientific Progress & Innovations, 2024)
Systematized the results of studying the species composition of harmful organisms that negatively affected the growth and productivity of corn under the conditions of the Ustymivka Research Station of Plant Breeding named V. Ya. Yuryev by Institute of Plant Breeding of the National Academy of Agrarian Sciences of Ukraine (UDSR). From 2021 to 2023, field and laboratory studies were conducted to identify samples resistant to major pests and diseases of corn under natural conditions for the agro-climatic conditions of the southern Forest-Steppe zone of Ukraine. The study material consisted of 110 corn samples of various origins from the UDSR collection and newly introduced samples, which were characterized by economically valuable indicators, namely: grain productivity of one plant, cob length, number of cobs per plant, 1000-grain weight, etc. The study results revealed the dominant diseases to be: Ustilago zeae (Beckm) (14 % of examined samples with an average infection of 0.2 % of plants); Soroshporium reilianum (Kuehn) (1.5 % of examined samples, with an average infection of 0.1 % of plants); Fusarium (70 % of samples with infection up to 30 % of cobs); Bacterial diseases (64 % of samples with infection up to 50 % of cobs); Ear rot (54 % of samples with infection up to 43 cobs). Sample damage by the Oscinella frit , O. pusilla ranged from 10 % to 82%, with damage levels varying from 0.5 to 5 points. This largely depended on weather conditions during the seedling period and the intensity of the initial growth of the sample. Ostrinia (Pyrausta) nubilalis Hb. annually damaged over 60 % of the samples, with an average of 1–5 larvae per plant. According to laboratory surveys, up to 23 % of the plots with 1–2 cobs per plot were damaged by Ostrinia (Pyrausta) nubilalis Hb.. The applied research methods enabled the differentiation of samples as sources of resistance to local populations of corn diseases and cobs, as well as to dominant phytophagous organisms in natural infection and invasion backgrounds. Among them were identified: samples with individual resistance to Ustilago zeae (Beckm) – 7 samples, to the Ostrinia (Pyrausta) nubilalis Hb. – 11 samples, to the Oscinella frit, O. pusilla – 9 samples. Group resistance to a complex of dominant diseases was characterized by 18 samples, and complex resistance to diseases and the Ostrinia (Pyrausta) nubilalis Hb. – 6 samples, which combined with high economically valuable indicators.